Gynocladius scalpellosus n. gen., n. sp. from Brazil (Diptera: Chironomidae: Orthocladiinae) - Mendes, H. F.; Sæther, O. A.; Andrade-Morraye, M. (Zootaxa, 2005)
Diagnoses of the female, pupa, and larva of Gynocladius n. gen. are given. Gynocladius scalpellosus sp. n. from Brazil is described from the female, pupa, and larva. A preliminary phylogenetic analysis places the genus as the sister group of Hanocladius Wang and Sæther from China and intermediate between Antillocladius Sæther and Compterosmittia Sæther. The females are apparently parthenogenetic.